2015
DOI: 10.1111/all.12587
|View full text |Cite
|
Sign up to set email alerts
|

Elevated D‐dimers in attacks of hereditary angioedema are not associated with increased thrombotic risk

Abstract: BackgroundRecommended management of attacks of hereditary angioedema (HAE) due to C1 esterase inhibitor (C1-INH) deficiency (C1-INH-HAE) includes therapy with exogenous C1INH. Thrombotic/thromboembolic events (TEE) have been reported with plasma-derived C1INH, but so far none with recombinant human C1INH (rhC1INH). This phase III, randomized, placebo (saline)-controlled study evaluated the safety of rhC1INH 50 IU/kg for the treatment of acute attacks in 74 patients with C1-INH-HAE.MethodsMonitoring for TEE and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 31 publications
6
52
4
Order By: Relevance
“…During episodes, bradykinin levels are elevated and thus increase vascular permeability. In spite of elevated factor XIIa levels and increased D-dimers during acute episodes, 189 hereditary angioedema is not associated with a heightened risk of thrombosis. This is likely related to preferential activation of the vasculoprotective kallikrein-kininogen pathway, evidenced by the increased bradykinin levels and resultant increased generation of PGI 2 , nitric oxide, and plasmin, with reduced TF expression.…”
Section: Contact Activation and Kallikrein-kininmentioning
confidence: 94%
“…During episodes, bradykinin levels are elevated and thus increase vascular permeability. In spite of elevated factor XIIa levels and increased D-dimers during acute episodes, 189 hereditary angioedema is not associated with a heightened risk of thrombosis. This is likely related to preferential activation of the vasculoprotective kallikrein-kininogen pathway, evidenced by the increased bradykinin levels and resultant increased generation of PGI 2 , nitric oxide, and plasmin, with reduced TF expression.…”
Section: Contact Activation and Kallikrein-kininmentioning
confidence: 94%
“…Recently, Bork and Witzke [48] showed that a shortened activated partial thromboplastin time (aPTT) may help to diagnose C1-INH-HAE and C1-INH-AAE when other tests are not available. aPTT is a routine and easy screening test for the "intrinsic" and "common" pathways of blood coagulation [49].…”
Section: Diagnosismentioning
confidence: 99%
“…These findings were corroborated by Reshef et al who evaluated D-dimer levels, which are consider biomarkers of thrombosis [81]. They reported that treatment with Ruconest did not affect D-dimer levels and was not associated with thrombotic events [82]. Use of any therapeutic protein may lead to the development of antibodies against the protein itself, its plasma counterpart or host-related impurities (HRI).…”
Section: Thrombogenicitymentioning
confidence: 82%